Analysis of the impact of urological malignant tumor surgery on child–pugh classification and prognosis in patients with liver cirrhosis - Wang, Yujie; Huang, Zhen; Zhang, Yu; Xue, Wenrui (Frontiers in Surgery, 2026)
ObjectivePatients with liver cirrhosis often present with relative contraindications to surgery, such as impaired coagulation function and thrombocytopenia.MethodsA total of 69 patients with urinary system malignancies who underwent radical resection under general anesthesia in the urology department of our hospital between 2013 and 2025 were included in this study. A Wilcoxon rank sum test was conducted to evaluate changes in the Child–Pugh(CP) classification before and after general anesthesia in patients with urinary system malignancies complicated by liver cirrhosis. The Pearson chi-square test was employed to assess the impact of various liver cirrhosis-related factors on the likelihood of CP classification downgrade.ResultsA total of 54 patients were classified as CP grade A prior to surgery. For patients with malignant tumors of urology combined with cirrhosis, the mean CP score (P < 0.0001) increased before and after surgery. There was no statistically significant effect of various liver cirrhosis-related factors on deterioration in the CP classification (P = 0.072). Univariate and multivariate analyses demonstrated that CP classification downgrading was significantly associated with overall survival (OS) (P = 0.006), cancer-specific survival (CSS) (P = 0.028), and disease-free survival (DFS) (P = 0.039). Compared with patients with a downgraded CP classification, patients without a downgraded CP classification had a more favorable survival curve (OS, P = 0.0034; CSS, P = 0.0194; DFS, P = 0.0296).ConclusionSurgery for malignant urinary system tumors in patients with CP grades A and B is generally considered safe. However, in some cases, the procedure may result in an elevated CP score and a downgrade in classification.